2013
DOI: 10.1371/journal.pone.0079595
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Post-Deployment Cognitive Performance and Symptom Recovery in U.S. Marines

Abstract: BackgroundComputerized neurocognitive testing (NCAT) has been proposed to be useful as a screening tool for post-deployment cognitive deficits in the setting of mild traumatic brain injury (mTBI). We assessed the clinical utility of post-injury/post-deployment Automated Neurocognitive Assessment Metric (ANAM) testing, using a longitudinal design to compare baseline ANAM tests with two post-deployment ANAM tests in a group of Marines who experienced combat during deployment.Methods and FindingsPost-deployment c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 32 publications
(43 reference statements)
2
10
0
Order By: Relevance
“…The group analyses (ie, between-and within-group differences) revealed results, not surprisingly, that were similar to previous reports. 21,23 Both groups performed similarly at T 1 (ie, between; mean effect was g = 0.05), and both groups had statistically significant decreases in scoring at T 2 when compared with their own group baseline at T 1 (ie, within) with effects of 0.32 and 0.56 (slightly below and above the RMPE of 0.41 for group differences) for the NCG and CNG, respectively. When performance was compared at T 2 , the CNG had significantly lower scores than the NCG (ie, between) for 5 of the 7 subtests; however, the mean effect (g = 0.27) for these significant differences was below the RMPE for group differences, suggesting that there were no meaningful differences between the groups.…”
Section: Reliable Changementioning
confidence: 87%
See 2 more Smart Citations
“…The group analyses (ie, between-and within-group differences) revealed results, not surprisingly, that were similar to previous reports. 21,23 Both groups performed similarly at T 1 (ie, between; mean effect was g = 0.05), and both groups had statistically significant decreases in scoring at T 2 when compared with their own group baseline at T 1 (ie, within) with effects of 0.32 and 0.56 (slightly below and above the RMPE of 0.41 for group differences) for the NCG and CNG, respectively. When performance was compared at T 2 , the CNG had significantly lower scores than the NCG (ie, between) for 5 of the 7 subtests; however, the mean effect (g = 0.27) for these significant differences was below the RMPE for group differences, suggesting that there were no meaningful differences between the groups.…”
Section: Reliable Changementioning
confidence: 87%
“…These studies reported conflicting results, possibly due to study design and methodological differences, which suggest that further research is warranted. [21][22][23] Haran et al 21 used traditional hypothesis testing to determine whether there were statistically significant different changes in pre-(ie, baseline) to postdeployment performance between SMs with self-reported concussion during deployment and nonconcussed controls. The results of the study revealed that the group with concussion had significant decreases in performance 2 to 8 weeks postdeployment (ie, during the chronic phase), which returned to baseline levels after 7 months postdeployment for all subtests, except for Simple Reaction Time Repeated (SRT2).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A diagnosis of a mild TBI (mTBI) suggests that most Service Members and Veterans will experience full cognitive and functional recovery [29, 69]. However, there are a number of individuals (~20 %) who continue to experience residual symptoms that could impact unit readiness, return to duty, safety of troop operations, and troop retention [13, 27, 67]. Thus, there is significant interest in improving diagnosis, prognostic accuracy, monitoring recovery or decline, and assessing treatment effects, especially for those experiencing persistent symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Beyond the development and expression of mental health difficulties, there is growing concern that stress may degrade neurocognitive performance and adversely affect operational performance. Neurocognitive deficits have been reported after repetitive military environmental exposures (e.g., blasts; Luethcke et al, 2011 ), stress-related mental disorders (Marx et al, 2009 ; Luethcke et al, 2011 ; Haran et al, 2013 ), or mild traumatic brain injury (mTBI; Spira et al, 2014 ; Dretsch et al, 2015 ). The Defense Automated Neurobehavioral Assessment (DANA) battery, developed as a clinical decision support tool, consists of a battery of neurocognitive tests as well as psychological assessments for field screening of PTSD and MDD (Lathan et al, 2013 ; Spira et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%